Authoritarian innovations: theoretical foundations and practical implications. Issue 6 (17th August 2020) - Pepinsky, Thomas
ABSTRACT: Curato and Fossati's concept of authoritarian innovations encourages scholars to look beyond the nominal categories in which we may classify political regimes and to focus instead on how political decisions constrain or open up the space for mass political participation. In this commentary, I amplify the editors' productive distinction between regimes and practices, outline the methodological implications of a meso-level approach to authoritarianism, and highlight how a practice-oriented approach complements a range of critical approaches to the supposed emancipatory potential of new media, economic growth, and other social and political phenomena. I conclude by stepping back from these applications of Curato and Fossati's framework to consider whether any measures that restricts public participation is inherently anti-democratic.